Prediksi Optimasi Produksi Galon di PDAM AMDK Tirta Moedal Kota Semarang Menggunakan Metode Monte Carlo - Siwi, Vincensius Pandu Galih Raka; Talitha, Tita (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The Regional Drinking Water Company (PDAM) Tirta Moedal of Semarang City faces challenges in optimizing the production of gallon-sized Packaged Drinking Water (AMDK) due to an imbalance between demand and production. This imbalance often results in insufficient production compared to demand, causing a buildup of fleet vehicles and delays in product delivery. This study aims to address this problem by using the Monte Carlo method, a simulation technique that utilizes random numbers and statistics to predict outcomes and solve complex problems. In this study, historical data on demand and production of gallon water were collected and analyzed to build a probability distribution model. Monte Carlo simulation was then applied to simulate various demand and production scenarios. The simulation results were used to identify the most likely scenarios and develop a production optimization plan. The results of the study show that by implementing the Monte Carlo method, PDAM Tirta Moedal can improve the efficiency of production planning and capacity management, so that it is able to meet market demand more efficiently and on time. The implementation of this method can also help reduce delays in product delivery, increase customer satisfaction, and improve overall business performance.